Identification Of Misconceptions In The Materialhydrocarbonsuse Three-Tier Diagnostic With Techniquecertainty Of Response Index (Cri) - Mutmainnah, Ulfah Nurul; Sukmawardani, Yulia; Supriatna, Ateng (JUPE : Jurnal Pendidikan Mandala, 2025)
This research aims to identify misconceptions in hydrocarbon materials by applying the Three- Tier Diagnostic method as a diagnostic tool for in-depth exploration. Involving students at a specific educational level, the study develops a three-tier diagnostic instrument that includes questions with varying levels of difficulty. Furthermore, the Certainty of Response Index (CRI) technique is applied to measure students' confidence levels in their answers. Quantitative and qualitative analysis of student responses is expected to provide a deep understanding of commonly occurring misconceptions and factors influencing students' confidence levels in their answers. The results of this research are anticipated to serve as a foundation for improving learning design and developing more effective teaching strategies in the context of hydrocarbon materials. The methodological contribution, particularly the use of the CRI technique, is expected to assist researchers and educators in evaluating not only students' conceptual accuracy but also their confidence levels in understanding the material. Consequently, this research is expected to make a positive contribution to enhancing the quality of chemistry education at the relevant educational level.